2011
DOI: 10.1063/1.3560469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sample processing parameters on thermal boundary conductance value in an Al/AlN system

Abstract: Articles you may be interested in Thermal conductivity and interfacial conductance of AlN particle reinforced metal matrix composites J. Appl. Phys. 109, 064907 (2011) Analysis of the acoustoelectric behavior of microwave frequency, temperature-compensated AlN-based multilayer coupling configurations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…There are several factors significantly affecting the heat conduction across the interface such as surface roughness [3,22], native oxide layer [22,23], dislocation [24] and intermixing layer [25]. The first three factors should have the same effects on our different samples because the Si substrates are the same for all of our measurements.…”
Section: Resultsmentioning
confidence: 98%
“…There are several factors significantly affecting the heat conduction across the interface such as surface roughness [3,22], native oxide layer [22,23], dislocation [24] and intermixing layer [25]. The first three factors should have the same effects on our different samples because the Si substrates are the same for all of our measurements.…”
Section: Resultsmentioning
confidence: 98%
“…the TBC is mainly governed by properties of the materials on either side of the interface, but several features of the interface itself can also have a substantial influence on the resulting performance. Examples of such features include: intermixing between the layer and substrate 11 , ion bombardment of the interface 12,13 , roughness 14,15 and chemical termination of the substrate [16][17][18][19] , all of which have an impact on the TBC. Recently, Losego et al showed that there is a link between the chemical bonding at an interface between gold and quartz and the TBC of this interface by adding Self Assembled Monolayers (SAMs) between these two materials 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The results for the conductivity of the Al 2 O 3 interlayer are then calculated by fitting the X/Y ratio of the obtained curves using Equation 6 and 7. The parameters allowed to vary are the conductivity of the Al 2 O 3 layer and that of the substrate since very small spot sizes are used, which is known to significantly reduce the measured conductivity of solids with mean free paths longer than the spot size . After measuring the apparent thermal conductivity k app of the Al 2 O 3 layer at each thickness d , the inverse of its equivalent apparent stack conductance, h −1 , is plotted against the thickness: happ=dkapp=dkint+1hbd …”
Section: Methodsmentioning
confidence: 99%
“…A further approach consists in using a Green's function formalism, either with harmonic interatomic potentials or with potentials calculated using first‐principles methods . The ability of this last method to account efficiently for an interfacial stiffness different from the bulk or the presence of foreign atoms at the interface makes it a promising method to calculate TBCs in real systems. Its main drawback is the computational cost of calculating real interatomic potentials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation